Penerapan Sanksi Pidana Terhadap Perbuatan Lalai Pengemudi Becak (Studi Putusan Nomor 494/PID.SUS/2018/PN.Ambon) - John Christian Tutuarima; John Dirk Pasalbessy; Erwin Ubwarin (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Along with the times, there are also increasing various types of transportation that function to meet human needs, one of which is the traditional rickshaw vehicle. Traditional pedicabs are one of the non-motorized vehicles that still survive in carrying out transportation for the community. In Indonesia, there are many traffic accidents that occur between rickshaws and other transportation, as well as the negligence of the rickshaw driver. Negligence occurs due to someone's inner attitude that does not heed the prohibition so that the actions committed objectively cause conditions that are prohibited by law. 2) Review and discuss the reasons for legal considerations so that the judge lightens the decision of the prosecutor's indictment. The research method used in analyzing and discussing the problem is the normative juridical research method, which is an approach that is carried out by studying library materials or literature studies. From the results of research carried out by researchers through a conceptual and statutory approach, the results are concluded based on Article 183 of the Criminal Procedure Code, a judge imposes a sentence on a person with at least two pieces of evidence and he gains confidence that the defendant is guilty of doing so. the witness's testimony and regret for his actions which have fulfilled the elements in Article 359 of the Criminal Code related to negligence which caused another person's death.